Lifestyle in Heart Health and Disease - Watson, Ronald R. (Ronald Ross); Zibadi, Sherma (Elsevier Ltd. : Academic Press, 2018)
Lifestyle and Heart Health and Disease provides a comprehensive evaluation of lifestyle factors that modify heart function and structure. It includes coverage of a wide range of lifestyle factors, including physical activity, alcohol, tobacco, drugs of abuse, nutrition and psychosocial factors. The book clearly presents the scientific evaluation of published research relating to general responses by scientists, physicians and patients, along with new research on the role of lifestyle in the prevention, amelioration and causation of cardiac remodeling and disease. Explains the pathogenic mechanisms of cardiovascular diseases and the targets of therapyPresents methods contained within the book that can be applied to the diagnosis of heart diseaseContains a concise summary with recommendations for actions and conclusionsProvides a one-stop-shopping synopsis of key ideas associated with many aspects of lifestyle